Rural Women’s Entrepreneurship Process: The Role of the Community Empowerment Trust Fund of Bandungan Subdistrict, Semarang Regency - Komala Inggarwati Efendy; Wiwik Suryani (Universitas Islam Nahdlatul Ulama Jepara, 2026)
Objective: This study examines the entrepreneurial process of rural productive women and the role of microfinance institutions, particularly community empowerment trust fund (DAPM), in supporting that process. Research Design & Methods: A qualitative approach was used through in-depth interviews with 24 women loan recipients from DAPM in Bandungan Sub-district, Semarang Regency, and focus group discussions with 10 women group leaders. Findings: Thematic analysis revealed three phases of women’s entrepreneurship—intention, action, and sustainability. Economic needs, family support, and access to microcredit emerged as key drivers, while limited capital and market access remained main challenges. DAPM played a significant role not only in providing collateral-free loans but also in fostering confidence, resilience, and social empowerment. Participation in DAPM programs led to improved household income and social interaction among rural women. Implications & Recommendations: Integrating financial and non-financial support such as training, mentoring, and marketing assistance is essential to enhance women’s business sustainability. Policymakers should promote inclusive microfinance models that strengthen both economic and social empowerment. Contribution & Value Added: This study contributes to understanding rural women’s entrepreneurship by presenting an empirically grounded model of the entrepreneurial process and demonstrating how microfinance can function as both an economic catalyst and a social empowerment tool in rural communities.